Pseudocyesis vera in a health institution, North Western Nigeria - Aremu Saad Bolakale; Abdullahi Ibrahim; Abdulrasaq Amusa (AOSIS, 2015)
Pseudocyesis was first reported in 19th Century and several others have been subsequently reported. The classes of the illness include Pseudocyesis vera, Delusional Pseudocyesis, Stimulated Pseudocyesis and Erroneous Pseudocyesis. This case report typifies Pseudocyesis vera called true pseudocyesis. It is said to be commoner in rural communities, where people don't have access to maternity services and where found they were not being used. It is authors' believe that such illness can be prevented with more enlightenment on advantages of use of available antenatal services.